VETERINARY SANITARY EXPERTISE OF MEAT PRODUCT IN RABBITS FEEDED WITH PROBIOKORM PROBIOTICS - Eshmatov G.X.; Ganiyev S. (PEDAGOGS, 2025)
• Bakhtiyorovich E. S., SaifiddinJakhongirUgli K. DIAGNOSIS OF PROTEIN METABOLISM DISORDERS IN FISH //American Journal of Agriculture and Horticulture Innovations. – 2023. – Т. 3. – №. – С. 04-12. • Qosimov S. J., Sh U. K. Hypovitaminos A And D In Young Animals //American Journal of Advanced Scientific Research. – 2025. – Т. 2. – №. – С. 79-84. • Eshburiyev S. B., Kasimov S. J., Aslonova M. A. Causes and symptoms of protein metabolism disorders in fish //Proceedings of international conference on scientific research in Natural and Social Sciences. – 2023. – Т. 2. – №. – С. 55-63. • Касимов С. Ж., Мамацалаева З. ИНФЕКЦИОННЫЙ БРОНХИТ ПТИЦ //Global Science Review. – 2025. – Т. 2. – №. 1. – С. 80-83. • Kasimov S. et al. The Pathomorphology Of Disorders Of Vitamins And Protein Metabolism In Fish //The American Journal of Veterinary Sciences and Wildlife Discovery. – 2021. – Т. 3. – №. – С. 9-12. • Eshmatov, G. E. (2022). Harmony of education and student devlopment in the process of physical education. • Eshmatov, G. X., Niyozov, H. B., Yusupov, O. S., & Nazarov, A. B. (2019). Ferula assafoetida herbaceous herb morphological parameters of blood of karakul sheep. ACADEMICIA: An International Multidisciplinary Research Journal, 9(4), 146-151. • O’g’li, E. (2019). Influence of herbaceous grain on Ferula assafoet on the quantitative and qualitative characteristics of snowflake rams sperm. Asian Journal of Multidimensional Research (AJMR), 8(11), 6-10. • Ниязов, Х. Б. ДЕЙСТВИЕ СЕМЯН ФЕРУЛЫ НА МОРФОЛОГИЧЕСКИЕ ПОКАЗАТЕЛИ КРОВИ И ПЛОДОВИТОСТЬ КРОЛИКОВ. Zbiór artykułów naukowych recenzowanych., 80.